Determinants of reserved shares allocation in an IPO - Tan, Ying Wen (2009)
This paper examines the reasons, trends and determinants for reserved shares allocation of firms in an initial public offering (IPO). We found that the main reason for allocating reserved shares is to recognize and reward those who have contributed to the success of the firm. Trend analysis revealed that firms allocating reserved shares displayed a general decreasing trend over the years. Furthermore, firms in the Agriculture, Commerce, Construction, and Transport/Storage/Communications sectors would be more likely to allocate reserved shares. In the eight years horizon of this study, percentages set aside to be allocated for reserved shares for firms across industries had also showed a gradual decreasing trend. Multiple and logistic regression analysis were used to identify statistically significant determinants for reserved shares allocation. Our findings indicate that smaller, older and less risky firms are more likely to favor reserved shares allocation as compensation.